The Making of Virtual Tours of Village Landscapes in the “Nationalism” Village Wonorejo - Praja Firdaus Nuryananda; A. Muammar Alawi (Nusantara Science and Technology Proceedings, 2022)
This community service is entitled "Creating a virtual village landscape tour in the "National" village of Wonorejo. The purpose of making a virtual tour as a promotional medium is to introduce, the market in visual form. Virtual tour as a form of location simulation that digitally displays sound, narration, and text is a medium that has been widely used because it is effective and efficient in marketing, especially in tourism. The implementation of the service in the Wonorejo village, the "national" tourism village, was held with two activities, namely: 1) virtual making with the stages of taking pictures that characterize the Wonorejo village landscape, 2) basic education and training on shooting (for virtual tours) involving several village officials who have basic visual technology skills. The training method with direct involvement or direct practice in the use of technological tools is more effective. So that the development or filling of virtual content can be done independently by the village as a form of continuity.